Surface roughness in rotary ultrasonic machining: hypotheses and their testing via experiments and simulations - Cong, Weilong; Pei, Zhijian J.; Deines, Timothy W.; Zhang, P. F.; Treadwell, C. (My University, 2013)
Rotary ultrasonic machining (RUM) is a nontraditional drilling process. It has been used to drill not only brittle but also ductile materials. It was observed that the surface roughness of the drilled hole near the entrance side was better than that near the exit side. However, explanations about this observation could not be found in the literature. This paper aims to provide explanations about this observation. It presents three hypotheses and their testing via experiments and simulations.
Keywords: Grinding; Hypothesis; Machining; Rotary ultrasonic machining; Stainless steel; Surface roughness